Scientific And Theoretical Basis Of Economic-Geographical Study Of The Standard Of Living Of The Population (Eurasian Journal of History, Geography and Economics, 2024)
The article describes the scientific and theoretical foundations of studying the standard of living of the population from an economic-geographical perspective, the improvement of the social and economic situation of the population within the framework of the interrelationship of territorial development and economic potential, and the factors affecting the standard of living of the population through economic-geographical factors, in particular, territorial resources, industry, transport and service sectors. The article also separately examines the measurements and indicators of living standards, as well as the methodology of scientific research conducted in this area, the specific characteristics of regions, their geographical location, and the influence of natural resources on the formation of the standard of living of the population.